-28x+24-3x-12=30

Simple and best practice solution for -28x+24-3x-12=30 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -28x+24-3x-12=30 equation:


Simplifying
-28x + 24 + -3x + -12 = 30

Reorder the terms:
24 + -12 + -28x + -3x = 30

Combine like terms: 24 + -12 = 12
12 + -28x + -3x = 30

Combine like terms: -28x + -3x = -31x
12 + -31x = 30

Solving
12 + -31x = 30

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + -31x = 30 + -12

Combine like terms: 12 + -12 = 0
0 + -31x = 30 + -12
-31x = 30 + -12

Combine like terms: 30 + -12 = 18
-31x = 18

Divide each side by '-31'.
x = -0.5806451613

Simplifying
x = -0.5806451613

See similar equations:

| 104x=3x+6 | | 17/2+1/2= | | 6a+3=3a+15 | | 0=2sinx*2cosx | | 2y+7x=-5 | | 2=4r+n | | 3+17+5x=7x+10 | | 99=2d-419 | | h(1)=5 | | -x^2+9x=16 | | 6(5y-8)-(4y+7)= | | 4(-7x+6)-3(x-2)=30 | | 8t^2+64=0 | | 3-2(4n-6)=5(n+4) | | -2(n+1)=0 | | X^4+20=21 | | 69+2u=-23 | | 8x-(3x-17)=52 | | 5y+2x=19 | | -2x+2=-7+17 | | 15-(-30s)=465 | | 3(x-1)4+7=19 | | 2s-3=9 | | Y=ln(1-x^2) | | Y=(18-9)*p | | x=23+9 | | 3=16x+15 | | 17-2(1-3x)4=5 | | h(-3)=-3 | | 8(-3n-7)+6(6+4n)=-24 | | -9h+32=-67 | | 5-m=131 |

Equations solver categories